Unwrapping the Global Financing Facility: understanding implications for women’s children’s and adolescent’s health through layered policy analysis - Kinney, Mary; Kwesiga, Doris; Lawn, Joy E.; Walmisley, Ulla; Kumar, Meghan Bruce; Kiendrébéogo, Joël; Wanduru, Phillip; Waiswa, Peter; Shamba, Donat; Baraka, Jitihada; Chivangue, Andes; Msemo, Georgina; et al. (Global health action, 2025)
The Global Financing Facility (GFF), launched in 2015, aims to catalyse funding for reproductive, maternal, newborn, child, and adolescent health, and nutrition. Few independent assessments have evaluated its processes and impact. We conducted a multi-layered policy analysis of GFF documents - the Investment Cases (ICs) and the GFF-linked World Bank Project Appraisal Documents (PADs) - examining the content of GFF documents for 28 countries, comparing four tracer themes (maternal and newborn health, adolescent health, community health, and quality), and analysing the policy processes in four country studies (Burkina Faso, Mozambique, Tanzania, and Uganda). From 2015 to 2022, GFF-linked PADs reported US\ 14.5 billion of funding across 26 countries through 30 PADs, with GFF contributing 4% to this value. GFF investments primarily focused on service delivery, governance, and performance-based financing. Countries received more targeted investments for maternal and newborn health and adolescent health linked to their burden of these tracer themes. Attention to community health and quality varied. ICs were broader than PADs and more inclusive in their development. Local contexts shaped policy processes. GFF supported priority-setting and learning; however, translating priorities into resourced actions proved challenging. Power dynamics influenced country ownership, donor coordination and resource mobilisation. The GFF is a significant opportunity to advance health for vulnerable populations. Progress in transparency and data use is evident, but accountability gaps, power imbalances, and limited engagement with civil society and private sector hinder national ownership. Further research is needed to determine GFF’s attribution to catalytic resource mobilization. Main findings: This multi-layered policy analysis of the Global Financing Facility for women’s, children’s, and adolescents’ health reveals US\ 14.5 billion in new funds (2015-2022) in 28 countries, mostly through World Bank lending and domestic resources, with country variability in the priorities mentioned, measured and funded and the political processes that shaped them.Added knowledge: Each layer of analysis shows unique aspects of the Global Financing Facility, starting with an investment mapping, then exploring the content of policy documents across themes, to finally understanding the policy process in four countries, showing that while it was technocratically led, it was also political, influenced by many actors, and contextual drivers.Global health impact for policy and action: Global Health Initiatives need to be held accountable for their commitments and ensure that a country-led approach is accompanied by transparent processes at every step in the policy process with broad stakeholder engagement and agreed national priorities. Main findings: This multi-layered policy analysis of the Global Financing Facility for women’s, children’s, and adolescents’ health reveals US$ 14.5 billion in new funds (2015-2022) in 28 countries, mostly through World Bank lending and domestic resources, with country variability in the priorities mentioned, measured and funded and the political processes that shaped them. Added knowledge: Each layer of analysis shows unique aspects of the Global Financing Facility, starting with an investment mapping, then exploring the content of policy documents across themes, to finally understanding the policy process in four countries, showing that while it was technocratically led, it was also political, influenced by many actors, and contextual drivers. Global health impact for policy and action: Global Health Initiatives need to be held accountable for their commitments and ensure that a country-led approach is accompanied by transparent processes at every step in the policy process with broad stakeholder engagement and agreed national priorities.
Gesehen am 06.11.2025